Approaches to the design of catalytic metallodrugs - Soldevila-Barreda, Joan J; Sadler, Peter J (Current opinion in chemical biology, 2015)
•How can metal catalysts be used for biochemical transformations?•Catalysis by metal complexes can even be achieved in cells.•Catalysis includes CC bond formation, deprotection/functional group modification.•Degradation of biomolecules and redox modulation can also be achieved.•Four classes of catalytic redox modulators are discussed.•Catalytic metallodrugs offer the prospect of low-dose therapy. Metal ions are known to act as catalytic centres in metallo-enzymes. On the other hand, low-molecular-weight metal complexes are widely used as catalysts in chemical systems. However, small catalysts do not have a large protein ligand to provide substrate selectivity and minimize catalyst poisoning. Despite the challenges that the lack of a protein ligand might pose, some success in the use of metal catalysts for biochemical transformations has been reported. Here, we present a brief overview of such reports, especially involving catalytic reactions in cells. Examples include CC bond formation, deprotection and functional group modification, degradation of biomolecules, and redox modulation. We discuss four classes of catalytic redox modulators: photosensitizers, superoxide dismutase mimics, thiol oxidants, and transfer hydrogenation catalysts. Catalytic metallodrugs offer the prospect of low-dose therapy and a challenging new design strategy for future exploration.